Pengaruh Tingkat Pengetahuan Masyarakat Terhadap Minat Menggunakan Produk Bank Syariah (Studi pada Masyarakat Desa Carebbu, Kec. Awangpone, Kab. Bone) - Kasmiati, Kasmiati; Zulkifli, Zulkifli; Hasbi, Hartas (Journal of Comprehensive Science, 2024)
Public knowledge about Islamic banks will also affect the public's view of Islamic banks themselves. Interest is an interest in something that can cause feelings of pleasure, interest, and prosperity. This study discusses the influence of the level of public knowledge on interest in using Islamic bank products. This research was conducted with the aim of finding out the level of public knowledge about using Islamic bank products. This study uses a quantitative research method. The data of this study used primary data with the distribution of questionnaires as many as 97 respondents. The sampling technique uses a simple random sampling technique. The results of this study show that there is a partial effect between the level of public knowledge on the interest in using Islamic bank products with a value of 15,280. Meanwhile, the coefficient test obtained a score of 70.8% and the rest was influenced by other factors. Thus, a small number of related variables are explained by the independent variables used in the study.